Contemporary Mask Theory: The Study of Behavior and Personality – A Behavioral Approach to Management and Accounting - Deri Firmansyah; Dwinanto Priyo Susetyo; Rahma Wahdiniwaty; M. Yani Syafei; Abdisamad Abdirahman Omar (Electronic Journal of Education, Social Economics and Technology, 2024)
The mask of theory speaks of something more vague than the face of nature. The contemporary theoretical mask in this study adopts Mask behavioral approach to management and accounting in organizations. The potential impact caused by the personality of an individual wrapped in falsehood behind the face of the mask on the organizational climate and organizational performance, was also reviewed. To meet this objective, systematic literature review in the style of narrative review (NR) is carried out on several journals that contain relevant content. Findings, behavior, and interactions in the organizational environment are also inseparable from masks or personas. If the connotation is negative by prioritizing pretense and falsehood, perhaps hypocrisy will grow and lose trust among individual employees, accountants and leadership or may be able to collapse team solidarity and organizational strength. On the basis of any fraud model, financial fraud in organizations is inseparable from the aspect of individual work behavior personally or as a work team or cooperation in other parties internally and externally, opportunities seem to exist to be created by using masks so that they can still be trusted by other parties so that they are not seen in realizing their negative ideas, There are certain patterns of behavior that individuals usually show when fraud is. The implication is that whenever it is necessary to have our initiation and sensitivity to the behavior and temptation of an elegant personality in a mask, of course this is for those who describe compromise with the face of hypocrisy. The novelty of the narrative model in this paper is also explained.